2018
DOI: 10.1016/j.hemonc.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

CD209-336A/G promotor polymorphism and its clinical associations in sickle cell disease Egyptian Pediatric patients

Abstract: We found no significant difference between our population of Egyptian SCD cases and controls regarding CD209 A>G polymorphism. Infections occurred more frequently among the heterozygous genotype (AG) and homozygous genotype (GG) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…CD209 encodes dendritic cell-specific ICAM3-grabbing non-integrin (DC-SIGN), and has been shown to bind various ligands including T-lymphocytes, thus contributing to activation of signal transduction pathways and recognition of infectious agents. Several studies have shown its polymorphic variants to be associated with tolerance or susceptibility to diseases, such as tuberculosis, schistosomiasis, leishmaniasis, and sickle-cell disease [23,27,30,[51][52][53], asserting that the G allele significantly increased the risk of disease. Our results confirm this observation, indicating that mutation of the CD209 gene has a considerable impact on malaria pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD209 encodes dendritic cell-specific ICAM3-grabbing non-integrin (DC-SIGN), and has been shown to bind various ligands including T-lymphocytes, thus contributing to activation of signal transduction pathways and recognition of infectious agents. Several studies have shown its polymorphic variants to be associated with tolerance or susceptibility to diseases, such as tuberculosis, schistosomiasis, leishmaniasis, and sickle-cell disease [23,27,30,[51][52][53], asserting that the G allele significantly increased the risk of disease. Our results confirm this observation, indicating that mutation of the CD209 gene has a considerable impact on malaria pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The CD209 protein has been shown to recognize pathogens through its N-terminal domain, binding to ligands on microbes in the process [25], as well as activating the signal transduction pathway in the process. Since DC's are an essential component for antigen presentation, and for initiation of the process mediating adaptive immune responses, its polymorphisms, especially the rs4804803 (snp -336G/A) gene promoter polymorphism, have been shown to modulate disease susceptibility or severity [26][27][28][29][30][31][32]. We have shown previously that this polymorphism tracks ethnicity, with significant genotypic and allelic diversity between African and American sickle-cell disease patients [27].…”
Section: Introductionmentioning
confidence: 98%
“…In SCD the spleen is damaged by the sickled blood cells and it is not able to remove bacteria from the blood thus making the patient susceptible for infections apart from the splenic dysfunction, CD209-336 A>G polymorphism also leads to a number of bacterial infections. Genotypic frequency of CD209-336 A>G polymorphism also varies among different ethnic population of SCD patients and CD209-336 A>G polymorphism and bacteria responsible for infection can be used as a predicator of susceptibility to infections in patients with SCD [25].…”
Section: Bacterial Infectionmentioning
confidence: 99%